Iowa RBA, November 27, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for November 27, 1995. Highlights of the update include sightings of Pine Siskins, Common Redpoll, Selasphorus type Hummingbird (Rufous Hummingbird), Varied Thrush, Evening Grosbeak, Long-tailed Duck and a Red-throated Loon. Epson - sheet feed/flatbed